Biochemical Changes in Hepatic Function of Petrol Station Attendants in Basrah. - Jabir, Majid S; Khalil, Omar A; Taqi, Zainab J; Hussain, Huda A (Al-Nahrain Journal of Science, 2018)
Previous studies on human and animals demonstrated that many of chemicals components of petroleum can affect the liver function. The present study investigated and evaluated the hepatotoxic effects of petroleum fumes and the changes in liver biochemical functions resulted from exposure to petrol and their derivatives by measuring the changes of liver enzymes and total serum bilirubin in 18 petrol workers station attendant in Basrah, Iraq. A corresponding 18healthy subjects were used as controls. Biochemical analyses on the serum samples were done after samples collection. Results are time exposure dependent. Our results showed the presence of a significant increase in the level of Glutamic-pyruvic transaminase (GOT), Glutamic-oxaloacetic transaminase (GPT), Alkaline phosphatase ALP and they related to the time of exposure to petroleum products especially for 3-6 years, and for 6-10 years, p value was p≤ 0.01, p≤ 0.001 respectively. Total serum bilirubin TSB for those workers which were exposed to petrol from six to ten years were also showed a significantly higher than the control. These effects may be directly related to time of exposure. The study suggests that long term inhalation of petrol fumes is associated with adverse effect on liver function.